2022
DOI: 10.3390/biomedicines10020385
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 Pathology and Prionic Behavior in Human Cellular Models of Alzheimer’s Disease Patients

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder for which there is currently no effective treatment. Despite advances in the molecular pathology of the characteristic histopathological markers of the disease (tau protein and β-amyloid), their translation to the clinic has not provided the expected results. Increasing evidences have demonstrated the presence of aggregates of TDP-43 (TAR DNA binding protein 43) in the postmortem brains of patients diagnosed with AD. The present research is focused on of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In consonance with the fact that AD is not only a brain disorder but also presents several peripheral and systemic abnormalities ( Wojsiat et al, 2015 ; Esteras et al, 2016 ), we recently reported alterations in TDP-43 homeostasis, including increased TDP-43 phosphorylation, truncation and cytoplasmic accumulation in immortalised lymphocytes derived from AD patients. Moreover, we observed an enrichment of a 25 kDa TDP-43 fragment in the extracellular medium from AD cells, and found that conditioned medium from lymphoblasts of severe AD induced TDP-43 pathology in healthy cells ( Cuevas et al, 2022 ). Here, we report that targeting TDP-43 phosphorylation with different kinase inhibitors seems to stop disease propagation.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In consonance with the fact that AD is not only a brain disorder but also presents several peripheral and systemic abnormalities ( Wojsiat et al, 2015 ; Esteras et al, 2016 ), we recently reported alterations in TDP-43 homeostasis, including increased TDP-43 phosphorylation, truncation and cytoplasmic accumulation in immortalised lymphocytes derived from AD patients. Moreover, we observed an enrichment of a 25 kDa TDP-43 fragment in the extracellular medium from AD cells, and found that conditioned medium from lymphoblasts of severe AD induced TDP-43 pathology in healthy cells ( Cuevas et al, 2022 ). Here, we report that targeting TDP-43 phosphorylation with different kinase inhibitors seems to stop disease propagation.…”
Section: Discussionmentioning
confidence: 88%
“…VNG1.47 and IGS2.7 have shown to be effective in the experimental treatment of lymphoblasts from ALS patients which are characterized by presenting TDP-43 hyperphosphorylated cytosolic aggregates, the main pathological hallmark of ALS ( Martinez-Gonzalez et al, 2020 ; Nozal et al, 2022 ). We have recently reported the presence of TDP-43 pathology in AD immortalized lymphocytes ( Cuevas et al, 2022 ). However, it was not explored whether small molecule protein kinases inhibitors would be able to modulate TDP-43 pathological hallmark in samples from AD patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations